Tinjauan Literatur tentang Instrumen untuk Mengukur Dukungan Ayah dalam Pemberian ASI - Rofi Khatul Janah; Hanifatur Rosyidah (Jurnal Skala Kesehatan, 2026)
Exclusive breastfeeding is important for child growth, but its coverage in Indonesia is still low. Father's support in the breastfeeding process has been identified as an important factor that can increase the success of exclusive breastfeeding. Therefore, a valid instrument is needed to measure this support. A systematic review was conducted on March 3, 2025, following the PRISMA guidelines. A literature search was conducted in the Pubmed database with search terms related to father's support and breastfeeding and according to the inclusion criteria. Of the 211 initial articles, 6 articles were selected for further analysis. The identified instruments were the Partner Breastfeeding Influence Scale (PBIS), Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), and Paternal Support Scale of Breastfeeding (PSSB) which have shown good validity and reliability in measuring father's support. It can be concluded that the measuring instruments used to measure father's support in breastfeeding include PBIS, BSES-SF, and PSSB which have been tested for validity and reliability in different contexts, and have shown good results. The author concludes that PBIS is an instrument that contains more items and has more complete content.